A real‐time method to simultaneously measure linear energy transfer and dose for proton therapy using organic scintillators. Issue 4 (7th March 2018) - Alsanea, Fahed; Therriault‐Proulx, Francois; Sawakuchi, Gabriel; Beddar, Sam
Abstract : Purpose: Currently, no detectors are capable of simultaneously measuring dose and linear energy transfer (LET) in real time. In this study, we evaluated the feasibility of exploiting the difference in the response of various organic plastic scintillation detectors to measure LET and dose in therapeutic proton beams. The hypothesis behind this work was that the ratio of the responses of different scintillators exposed to the same proton beam can be used to obtain a LET vs ratio calibration curve that can then be used to infer LET under any other measurement conditions. Methods: We first used similar scintillators with different ionization quenching factors. LET values for different irradiation conditions were calculated using a validated Monte Carlo model of the proton beam line. The quenching factors in the Birks equation for different scintillators as a function of LET were obtained from measurements in a 100‐MeV pristine proton beam. We then used four different organic scintillation materials — polystyrene (BCF‐12), poly (methyl methacrylate), polyvinyltoluene, and a liquid scintillator — for which the LET response varied with regard to not only quenching but also differences in material density and relative stopping power. We simultaneously exposed the four different organic scintillators and a plane–parallel ion chamber to passively scattered proton beams at fluence‐averaged LET. Comparisons to the expected values obtained from the Monte Carlo simulations were made on the basis of both dose and LET. Results: The maximum difference in the quenching factor was 20%, resulting in a 5% change in LET with a response ratio over a range of 5 keV/μm. Among all the scintillators investigated, the ratio of PMMA to BCF‐12 provided the best correlation with LET values and was therefore used to construct the LET calibration curve. The expected LET values in the validation set were within 2% ± 6%, which resulted in dose accuracy of 1.5% ± 5.8% for the range of LET values investigated in this work. Conclusions: We demonstrated the feasibility of using the ratio of the light outputs of two organic scintillators to simultaneously measure LET and dose in therapeutic proton beams for fluence‐averaged LET values from 0.47 to 1.26 keV/μm. Further studies are needed to verify the response for higher LET values and the reproducibility of this method.